2021
DOI: 10.1038/s41598-020-80634-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Lactobacillus plantarum VAL6 to challenges of pH and sodium chloride stresses

Abstract: To investigate the effect of environmental stresses on the exopolysaccharide biosynthesis, after 24 h of culture at 37 °C with pH 6.8 and without sodium chloride, Lactobacillus plantarum VAL6 was exposed to different stress conditions, including pH (pHs of 3 and 8) and high sodium chloride concentration treatments. The results found that Lactobacillus plantarum VAL6 exposed to stress at pH 3 for 3 h gives the highest exopolysaccharide yield (50.44 g/L) which is 6.4 fold higher than non-stress. Under pH and sod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 53 publications
1
14
0
1
Order By: Relevance
“…S7 ). A recent study has shown that the exopolysaccharides (EPS) production could be upregulated in L. plantarum cells grown at acidic pH, which supports our observation 28 . Biofilm formation by probiotic species is a propitious tactic to control pathogenic biofilms, which is relatively based on the competitive-exclusion principle 29 , 30 .…”
Section: Discussionsupporting
confidence: 92%
“…S7 ). A recent study has shown that the exopolysaccharides (EPS) production could be upregulated in L. plantarum cells grown at acidic pH, which supports our observation 28 . Biofilm formation by probiotic species is a propitious tactic to control pathogenic biofilms, which is relatively based on the competitive-exclusion principle 29 , 30 .…”
Section: Discussionsupporting
confidence: 92%
“…Some of these units could belong to the HePS, thus confirming the previous hypothesis. Finally, albeit the hexose units are frequent in lactobacilli EPS [12] , the presence of arabinose has been detected and associated to bacterial stress resistance [44] .…”
Section: Resultsmentioning
confidence: 99%
“…The secretion of EPS is also recognized as a fundamental microbial adaptation to salinity, providing osmotic tolerance and limiting dehydration ( 35 ). The composition of excreted EPS can change in response to salinity fluctuations ( 36 38 ), as has been observed in the halophilic archaeon Haloferax volcanii when salinity decreases ( 39 ). A similar adaptation strategy observed within halophilic archaea is the production and inclusion of isoprenoid derivatives and carotenoids into lipid membranes, which helps in maintaining their fluidity in response to changes in the osmotic conditions ( 40 ).…”
Section: Introductionmentioning
confidence: 92%